In Silico Screening 2019-Coronavirus Inhibitors by SARS Template-Based Molecular Docking on ANTI-HIV Drugs - Hoang, Minh Hao (Journal of Technical Education Science, 2022)
Proteases or proteolytic enzymes are effective targets for developing antiviral drugs. The chymotrypsin-like cysteine protease (3CLpro), known as the main protease (Mpro) of severe acute respiratory syndrome coronavirus (SARS-CoV) plays an essential role in the proteolytic processing of viruses, and it is an effective target for anti-SARS drug development. An outbreak of novel coronavirus, named 2019-nCoV that occurred in Wuhan, China, has been identified as the cause of the disease and spread rapidly in multiple countries. There are no drugs approved to be an effective treatment for the 2019-nCoV yet. The result of sequence alignment revealed that the 2019-nCov Mpro shows 96% similarity with that of SARS-CoV 3CLpro (SARS Mpro). This is a potential discovery for developing 2019-nCov inhibitors. In order to find more potential inhibitors of the 2019-nCov Mpro protein, we selected SARS-CoV 3CLpro (PDB ID: 2GTB) as a template to perform molecular docking on 10 approved anti-HIV drugs. The docking results revealed that the SARS Mpro gave the highest binding affinity for saquinavir with a binding energy of -29.21 kcal/mol. Anti-HIV drugs darunavir (-23.43 kcal/mol), indinavir (-22.87 kcal/mol), and nelfinavir (-21.54 kcal/mol) also showed good binding modes with the active sites of protein, indicating that they may have the potential to be used as anti-COVID-19 clinical drugs. The observations would contribute more drug candidates that could interact with key residues of 2019-nCov Mpro similarly to the existing inhibitors against SARS-CoV 3CLpro.